Maternal cardiac deceleration capacity: a novel insight into maternal autonomic function in pregnancies complicated by hypertensive disorders and intrauterine growth restriction. (November 2016) - Casati, D.; Stampalija, T.; Ferrazzi, E.; Alberti, A.M.; Scebba, I.; Paganelli, A.; Di Martino, D.; Muggiasca, M.L.; Bauer, A.
Abstract: Objective: To explore maternal cardiac deceleration capacity (DC), a marker of autonomic function derived from electrocardiographic (ECG) signals, in pregnancies complicated by intrauterine growth restriction (IUGR) and hypertensive disorders of pregnancy (HDP) associated to IUGR (HDP-IUGR) or to appropriate for gestational age fetal growth (HDP-AGAf). Methods: Prospective single center case-control study conducted at Buzzi Children's Hospital, Milan. Maternal ECGs were analyzed by Phase Rectified Signal Averaging (PRSA) method to obtain cardiac DC in women with: HDP-IUGR, HDP-AGAf, severe-IUGR, mild-IUGR and uncomplicated pregnancies. IUGR was defined as abdominal circumference <5th centile; severe-IUGR was associated with umbilical artery Doppler pulsatility index >2 standard deviations. Non-parametric tests were adopted. Results: 269 women were recruited. Women with HDP-IUGR ( n  = 35) showed significantly higher cardiac DC compared both to controls ( n  = 141) ( p  = 0.003) and women with HDP-AGAf ( n  = 18) ( p  = 0.01). Women with severe-IUGR ( n  = 14) showed significantly higher DC than controls ( p  = 0.01). Women with mild-IUGR ( n  = 61) as well as women with HDP-AGAf showed no differences in DC compared to controls (both p  = 0.3). Conclusions: Women with pregnancy complicated by severe placental failure, such as HDP-IUGR and severe IUGR, show significant autonomic alterations, as indicated by elevated cardiac DC. On the contrary, pregnancy complications such as HDP-AGAf and mild IUGR show no impact on maternal autonomic balance. We present a new approach to explore maternal autonomic cardiovascular regulation that might reflect the severity of placental vascular insufficiency.